Corneal Crosslinking to Regress Pathologic Corneal Neovascularization Before High-Risk Keratoplasty. Issue 2 (February 2021) - Schaub, Friederike; Hou, Yanhong; Zhang, Wei; Bock, Felix; Hos, Deniz; Cursiefen, Claus
Abstract : Purpose: Corneal neovascularization is the main risk factor for graft rejection after high-risk penetrating keratoplasty (PK). Corneal crosslinking (CXL) has been shown to regress pathological corneal blood and lymphatic vessels and to reduce the risk of graft rejection after high-risk PK experimentally in mice. The aim of this work was to analyze whether CXL is also able to regress corneal neovascularization in patients and is a safe procedure in the context of high-risk PK. Methods: This retrospective case series included 5 patients with progressive corneal neovascularization and the need for high-risk PK because of graft rejection and/or keratitis that received CXL and PK between April 2019 and January 2020. CXL was performed before or in combination with PK and the effect of CXL on corneal neovascularization was assessed morphometrically on slit-lamp images. Patients were followed up to determine the incidence of adverse effects and graft rejection. Results: In 1 case, peripheral corneal CXL was performed first as a single procedure, followed by an additional peripheral CXL procedure combined with PK. In all other cases, peripheral CXL was directly combined with PK. No intraoperative or postoperative complications were observed. Peripheral CXL resulted in a reduction of corneal neovascularization (mean reduction of 70.5% ± 22.7%). Revascularization was not observed. All transplants remained clear and without immune reactions (mean follow-up 16.4 ± 14.9 weeks, range 4–42 weeks). Conclusions: CXL is able to reduce pathological corneal neovascularization and might therefore be a novel treatment option to improve graft survival after high-risk PK.